MRI-Defined Osteonecrosis Extent After Locked Plate Fixation of Proximal Humeral Fractures: Correlation with Shoulder Motion and Radiographic Severity - Ahmet Serhat Aydin; Dağhan Koyuncu; Alper Şükrü Kendirici; Mert Ballı; Ali Erşen; Görkem Durak; Memduh Dursun (Journal of Clinical Medicine, 2026)
Background/Objectives: Humeral head osteonecrosis is a recognised complication of locked plate fixation for proximal humeral fractures, yet the significance of necrotic lesion extent is poorly characterised. This study quantified MRI-defined osteonecrosis extent and its associations with radiographic severity, shoulder motion, and functional outcomes. Methods: Twenty-five patients with Neer three- or four-part proximal humeral fractures treated by locked plate fixation between 2010 and 2022 were retrospectively reviewed. Shoulder range of motion, Constant score, American Shoulder and Elbow Surgeons (ASES) score, and visual analogue scale (VAS) pain were assessed. Osteonecrosis severity was graded by the Cruess classification. Necrotic extent was quantified on MRI using an angle-based method on coronal and sagittal images; associations were assessed by simple linear regression among patients with confirmed osteonecrosis (n = 12). Results: At a mean follow-up of 85.4 ± 34.1 months, osteonecrosis was present in 12 of 25 patients (48%). Affected patients had lower shoulder abduction (96.7 ± 27.1° vs. 121.8 ± 29.2°; mean difference −25.1°, 95% CI −47.9 to −2.3; p = 0.031), internal rotation (48.3 ± 15.9° vs. 66.4 ± 15.5°; mean difference −18.1°, 95% CI −32.1 to −4.1; p = 0.014), and external rotation (36.7 ± 16.7° vs. 51.8 ± 26.4°; mean difference −15.1°, 95% CI −29.5 to −0.7; p = 0.041). Functional scores did not differ. Among patients with osteonecrosis (n = 12), greater necrotic angle correlated with higher Cruess stage and reduced abduction (β = −0.141; 95% CI −0.259 to −0.024; p = 0.020). Conclusions: MRI-defined osteonecrosis extent correlates with radiographic severity and reduced shoulder motion after locked plate fixation. Larger necrotic lesions are linked to decreased abduction, with no clear relationship to global functional scores. Quantitative MRI may provide useful information on the structural severity of post-traumatic humeral head osteonecrosis.